Membangun Alam Pikir Ekoteologis: Sebuah Refleksi Teologis Atas Tesis Lynn White - Bestian Simangunsong (Institut Agama Kristen Negeri Tarutung, 2021)
AbstractEcological destruction is a global phenomenon that demands a paradigm change and a new attitude towards the earth as the shared home of all creation. The increasingly of environmental damage is influenced by human paradigms and actions, resulting in exploitative and destructive actions against the earth. Historian Lynn White points out that Western Christian traditions contribute to today's ecological damage. White proposed Francis of Asisi as a